Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Silicon photonics 90° optical hybrid design for coherent receivers - Gudyriev, Sergiy; Scheytt, Christoph (Kleinheubacher Tagung 2015)
The recent rapid development of silicon photonics technology has spurred the process of on-chip integration of all kinds of opto-electronic components. One of the most common components of such type is the opto-electrical receiver. The monolithic implementation of the receiver could potentially have lower power consumption, higher sensitivity and bandwidth due to very short diode to amplifier connection length, which has very low parasitic capacitance and series resistance. The SiGe photodiode itself is also very compact, thus lowering the junction capacitance and improving its bandwidth. Among the different optical communication systems, coherent transmission lately received a lot of attention due to the rising requirements of the optical link capacity, and it was shown that this particular approach could benefit greatly from the monolithic integration, since the major component required for the demodulation on the receiver side – 90° optical hybrid – could be implemented fully passive and directly on the same chip as the receiver itself, together with digital post-processing circuitry. Despite the initial complexity of the modulation scheme, advanced silicon photonics components like this optical hybrid could make coherent transmission attractive even for short-range optical links. I would like to present the actual designs, implementation and measurement results of 90° fully passive optical hybrids, implemented in the IHP SG25PIC (passive photonics IC) technology. One of the designs is based on 4x4 multimode interferometer (MMI). The other one is based on two separate 2x2 MMIs with additional delay element. The final designs didn’t require any additional tuning after fabrication and have shown sufficient precision and performance for a coherent system design. The results of this work were later used for the design of monolithic coherent receiver.

Self-organized assemblies of colloidal particles obtained from an aligned chromonic liquid crystal dispersion - Zimmermann, Natalie; Jünnemann-Held, Gisela; Collings, Peter J.; Kitzerow, Heinz-Siegfried (Soft Matter)
Keywords: Condensed Matter Physics; General Chemistry

Chemically and thermally stable, emissive carbon dots as viable alternatives to semiconductor quantum dots for emissive nematic liquid crystal–nanoparticle mixtures with lower threshold voltage - Urbanski, Martin; Mirzaei, Javad; Sharma, Anshul; Hofmann, Daniel; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Electrically tunable zero dispersion wavelengths in photonic crystal fibers filled with a dual frequency addressable liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Storage of hyperentanglement in a solid-state quantum memory - Tiranov, Alexey; Lavoie, Jonathan; Ferrier, Alban; Goldner, Philippe; Verma, Varun B.; Nam, Sae Woo; Mirin, Richard P.; Lita, Adriana E.; Marsili, Francesco; Herrmann, Harald; Silberhorn, Christine; Gisin, Nicolas; et al. (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (SPIE Proceedings Vol. 9361: Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Raman scattering efficiency in LiTaO3 and LiNbO3 crystals - Sanna, Simone; Neufeld, Sergej; Rüsing, Michael; Berth, Gerhard; Zrenner, Artur; Schmidt, Wolf Gero (Physical Review B)
LiTaO3 and LiNbO3 crystals are investigated here in a combined experimental and theoretical study that uses Raman spectroscopy in a complete set of scattering geometries and corresponding density-functional theory calculations to provide microscopic information on their vibrational properties. The Raman scattering efficiency is computed from first principles in order to univocally assign the measured Raman peaks to the calculated eigenvectors. Measured and calculated Raman spectra are shown to be in qualitative agreement and confirm the mode assignment by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)], thus finally settling a long debate. While the two crystals show rather similar vibrational properties overall, the E-TO9 mode is markedly different in the two oxides. The deviations are explained by a different anion-cation bond type in LiTaO3 and LiNbO3 crystals.

Magnetoconductance of a magnetic double barrier in a quantum wire - Schüler, B.; Cerchez, M.; Xu, Hengyi; Heinzel, T.; Reuter, Dirk; Wieck, A.D. (Superlattices and Microstructures)

Confocal shift interferometry of coherent emission from trapped dipolar excitons - Repp, J.; Schinner, G. J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Wurstbauer, U.; Kotthaus, J. P.; Holleitner, A. W. (Applied Physics Letters)

Observation of quantum states without a semiclassical equivalence bound by a magnetic field gradient - Schüler, B.; Cerchez, M.; Xu, Hengyi; Schluck, J.; Heinzel, T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Spin-flip Raman scattering of the resident electron in singly charged (In,Ga)As/GaAs quantum dot ensembles - Debus, J.; Sapega, V. F.; Dunker, D.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

All-optical implementation of a dynamic decoupling protocol for hole spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Excitation of complex spin dynamics patterns in a quantum-dot electron spin ensemble - Varwig, S.; Yugova, I. A.; René, A.; Kazimierczuk, T.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Magnetic properties of Gd-doped GaN - Shvarkov, Stepan; Ludwig, Astrid; Wieck, Andreas Dirk; Cordier, Yvon; Ney, Andreas; Hardtdegen, Hilde; Haab, Anna; Trampert, Achim; Ranchal, Rocío; Herfort, Jens; Becker, Hans-Werner; Rogalla, Detlef; et al. (physica status solidi (b))

Time and spatially resolved electron spin detection in semiconductor heterostructures by magneto-optical Kerr microscopy - Henn, Tobias; Kießling, Tobias; Molenkamp, Laurens W.; Reuter, Dirk; Wieck, Andreas D.; Biermann, Klaus; Santos, Paulo V.; Ossau, Wolfgang (physica status solidi (b))

Optically controlled initialization and read-out of an electron spin bound to a fluorine donor in ZnSe - Kim, Y.M.; Sleiter, D.; Sanaka, K.; Reuter, Dirk; Lischka, K.; Yamamoto, Y.; Pawlis, A. (Current Applied Physics)

Structural, optical, and magnetic properties of highly-resistive Sm-implanted GaN thin films - Lo, Fang-Yuh; Huang, Cheng-De; Chou, Kai-Chieh; Guo, Jhong-Yu; Liu, Hsiang-Lin; Ney, Verena; Ney, Andreas; Shvarkov, Stepan; Pezzagna, Sébastien; Reuter, Dirk; Chia, Chi-Ta; Chern, Ming-Yau; et al. (Journal of Applied Physics)

Determining the stability and activation energy of Si acceptors in AlGaAs using quantum interference in an open hole quantum dot - Carrad, D. J.; Burke, A. M.; Klochan, O.; See, A. M.; Hamilton, A. R.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Micolich, A. P. (Physical Review B)

Nuclear magnetic resonances in (In,Ga)As/GaAs quantum dots studied by resonant optical pumping - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Petrov, M. Yu.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

All-optical tomography of electron spins in (In,Ga)As quantum dots - Varwig, S.; René, A.; Economou, Sophia E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review B)

Direct Quantitative Electrical Measurement of Many-Body Interactions in Exciton Complexes in InAs Quantum Dots - Labud, P. A.; Ludwig, A.; Wieck, A. D.; Bester, G.; Reuter, Dirk (Physical Review Letters)

Non-polar GaN quantum dots integrated into high quality cubic AlN microdisks - Bürger, M.; Callsen, G.; Kure, T.; Hoffmann, A.; Pawlis, A.; Reuter, Dirk; As, D. J. (physica status solidi (c))

Manipulating wave propagation with geometric metasurfaces: fundamentals and applications - Huang, Lingling; Chen, Xianzhong; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Zentgraf, Thomas; Zhang, Shuang (Plasmonics)

Optical spectrum, perceived color, refractive index, and non-adiabatic dynamics of the photochromic diarylethene CMTE - Wiebeler, Christian; Bader, Christina A.; Meier, Cedrik; Schumacher, Stefan (Phys. Chem. Chem. Phys.)

Polarization properties of single zinc-blende GaN/AlN quantum dots - Sergent, S.; Kako, S.; Bürger, M.; Schupp, T.; As, Donat Josef; Arakawa, Y. (Physical Review B)

Radio Frequency Electromechanical Control over a Surface Plasmon Polariton Coupler - Ruppert, Claudia; Förster, Frederike; Zrenner, Artur; Kinzel, Jörg B.; Wixforth, Achim; Krenner, Hubert J.; Betz, Markus (ACS Photonics)
We explore the impact of ∼500 MHz surface acoustic waves traveling across a commensurable plasmonic grating coupler. A stroboscopic technique involving surface acoustic waves synchronized to a modelocked optical source allows to time-resolve the dynamical impact of the electromechanically induced perturbation. The surface acoustic wave periodically enhances or decreases the surface ripple of the static grating. Most remarkably, the dynamic surface deformation deliberately modulates the coupler’s efficiency by ±2% during the ∼2 ns acoustic cycle.
Keywords: nanomechanics; plasmonics; surface acoustic waves; surface plasmon polaritons

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Hochauflösende Holografie - Zentgraf, Thomas (Physik in unserer Zeit)

mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Electro-optic tuning of split ring resonators embedded in a liquid crystal - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Letters)

Effect of Alignment on a Liquid Crystal/Split-Ring Resonator Metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (ChemPhysChem)

Polycyclic Aromatic Hydrocarbons Obtained by Lateral Core Extension of Mesogenic Perylenes: Absorption and Optoelectronic Properties - Vollbrecht, Joachim; Bock, Harald; Wiebeler, Christian; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (Chemistry - A European Journal)

Polymer-stabilized blue phases: promising mesophases for a new generation of liquid crystal displays - Nordendorf, G.; Hoischen, A.; Schmidtke, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Columnar molecular aggregation in the aqueous solutions of disodium cromoglycate - Agra-Kooijman, Dena M.; Singh, Gautam; Lorenz, Alexander; Collings, Peter J.; Kitzerow, Heinz-Siegfried; Kumar, Satyendra (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Synthesis of Liquid Crystal Silane-Functionalized Gold Nanoparticles and Their Effects on the Optical and Electro-Optic Properties of a Structurally Related Nematic Liquid Crystal - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics